Implementation of the Standard Inpatient Class Policy at RSUP Dr. Tadjuddin Makassar - Muhammad Alwy Arifin; Andi Luthfiyyah Anna; Dian Saputra Marzuki; Sukri Palutturi; Ryryn Suryaman Prana Putra (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Background: Based on Presidential Regulation No. 59 of 2024, which replaces Presidential Regulation No. 82 of 2018 on Health Insurance, the implementation of the Standard Inpatient Class (KRIS) is mandated for four types of hospitals in Indonesia, including RSUP Dr. Tadjuddin Chalid Makassar. The KRIS policy must be implemented in all hospitals in Indonesia cooperating with BPJS Health by June 30, 2025. However, the current implementation of KRIS primarily focuses on adjusting medical facilities and infrastructure toward a single class. To analyze the implementation of the KRIS policy at RSUP Dr. Tadjuddin Chalid Makassar in 2024 based on Input and Process aspects. Method: This study employed descriptive research with a qualitative approach, using interviews, observations, and document reviews conducted from February to March 2024 at RSUP Dr. Tadjuddin Chalid Makassar. Eleven informants were selected using purposive sampling. Result: The